Implementasi Hukum Waris Islam Di Persatuan Kematian ‎ Al Ikhlas Jl. H. Arief Tembilahan Hulu Tahun 2022‎ - Caca Kurniasari; Herdiansyah; Nor Hafizah; Putri Roztavia Febrianti; Raymond Ferynaldo (Indra Institute Research & Publication, 2023)
The death association of Al-Ikhlas referred to above is a group of people formed to achieve a common goal. Where the purpose of forming the Al-Ikhlas death association is to help members who are members of it in the event of death. This association provides compensation in the form of funds obtained through the contributions of each member to families who have died in order to make it easier for the family to organize the management of the remains. The Al-Ikhlas Death Association was founded in 2015 which was initiated by one of the religious leaders on Jl. H. Arief Tembilahan Hulu. Untilnow, the Al-Ikhlas death association has 284 members. This research was conducted to understand and examine the implementation of Islamic Inheritance Law in the Al-Ikhlas death association Jln. H. Arief Tembilahan Hulu, 2022. The type of research applied is empirical legal research (socio-legal) or sociological jurisprudence. Based on the results of the research, it was found that in the communion community with the death of Al-Ikhlas Jln. H. Arief Tembilahan Hulu, in 2022 the law of inheritance explains that there is an impact of Islamic inheritance law on the inheritance law of the fellowship of Al-Ikhlas's death Jln. H. Arief Tembilahan Hulu, 2022. Its application in the Al-Ikhlas death fellowship community Jln. H. Arief Tembilahan Hulu, in 2022 he has implemented the provisions contained in the Islamic Inheritance Law.